(untitled) (Proceedings of International Educators Conference, 2024)
Conseptual analysis and concept are interrelated,set of ideas with a single rule.The concept is the essence of the concept embodied in the structural forms reflected in the image,content and sign.The concept appears in the text as whole and serves to reveal the content reflected in the text.The image og the object that forms the basis of the concept is clear enough,and its secondary parts are abstract,and they interact around a single basis.